Bilateral facial synkinesis in leprosy - Malhotra, Hardeep Singh (BMJ Publishing Group, 2012)
Leprosy is an important cause of cranial nerve palsy in endemic areas where it may be seen in upto 17.6% patients. The authors herein describe a rare case of bilaterally symmetrical facial synkinesis with video documentation and modified blink reflex. A 35-year-old gentleman presented with numbness involving right half of his face for 8 months and abnormal stretching sensations over both sides of his nose for one and a half months. Sensory and motor involvement of the right trigeminal nerve was detected along with bilaterally symmetrical facial synkinesis involving orbicularis oculi and nasalis. R(1) and R(2) responses consistent with mis-reinnervation were recorded on the left-side using orbicularis oculi and nasalis muscles. Skin biopsy revealed acid-fast bacilli and sural nerve biopsy, the presence of granulomas. After 3 months of follow-up on WHO multi-drug therapy, an improvement in facial sensations was observed but without any change in facial synkinetic movements.